At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
if we're changing the subject to t, we want to get t on it's own.
S = P(1 + rt)
Since we can't do anything with the parenthesis, we have to start with the division/multiplication. Divide both sides by P:
S = 1 + rt
P
Next we want to get rid of the 1, so subtract 1 from both sides:
S - 1 = rt
P
finally, divide both sides by r
(S/P) - 1 = t
r
so:
t = (S/P) - 1
r
S = P(1 + rt)
Since we can't do anything with the parenthesis, we have to start with the division/multiplication. Divide both sides by P:
S = 1 + rt
P
Next we want to get rid of the 1, so subtract 1 from both sides:
S - 1 = rt
P
finally, divide both sides by r
(S/P) - 1 = t
r
so:
t = (S/P) - 1
r
so basically we want to get t by itself on one side
so s=p(1+rt)
divide both sdies by p
s/p=1+rt
subtract 1
(s/p)-1=rt
divide by r
[(s/p)-1]/r=t
so s=p(1+rt)
divide both sdies by p
s/p=1+rt
subtract 1
(s/p)-1=rt
divide by r
[(s/p)-1]/r=t
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.